Emergency situations supported by context–aware and application streaming technologies. (30th May 2013) - Bernal, Jose Felipe Mejia; Falcarin, Paolo; Ardito, Luca; Rocha, Oscar Rodríguez; Morisio, Maurizio; Pistillo, Francesco; Giovanelli, Flavio
Emergency Telecommunications (EMTEL) deal with provisioning of telecommunications services in emergency situations; these can range from an individual in a state of personal emergency (with need to make an emergency call due to sudden illness, traffic accident, fire) to a very broad perspective of serious disruptions (earthquakes, floods, terrorist attacks). EMTEL covers the telecommunications needs of public safety resources, like: police, fire–fighters, ambulances and other medical services: such services usually rely on dedicated networks and equipment. We realised PICO (control platforms and delivery of services in converged networks) a platform for service delivery and emergency management on public telecommunications networks. PICO platform leverages on application streaming on Android OS and a context–aware system for fixed–mobile convergence based on IP Multimedia Subsystem (IMS).